Development an e-learning environment for CSE-110 at BRAC university - Hasnat, Farhana; Ferdous, Tanjila (BRAC University, 2010)
This thesis report is submitted in partial fulfillment of the requirements for the degree of Bachelor of Science in Computer Science and Engineering, 2009.